2013
DOI: 10.1038/bmt.2013.50
|View full text |Cite
|
Sign up to set email alerts
|

Matched unrelated or matched sibling donors result in comparable outcomes after non-myeloablative HSCT in patients with AML or MDS

Abstract: The impact of allelic HLA matching in patients with AML and myelodysplastic syndrome (MDS) who receive allogeneic PBSC after a reduced-intensity conditioning (RIC) regimen is unclear. From January 2000 to December 2010, 108 consecutive patients with AML (n ¼ 63) and MDS (n ¼ 45) received PBSC after RIC in our center, either from siblings (n ¼ 70) or from matched unrelated donors (MUD; 10/10 high resolution, n ¼ 38). Conditioning regimen was fludarabine based in 95% of patients and GvHD prophylaxis was mostly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…Several studies confirm these data, showing similar outcomes regardless of donor type. [18][19][20] We found a survival benefit with lower dose ATG-F. Previous studies, of which some are published as abstracts only, found some advantage for ATG treatment.…”
Section: Discussionsupporting
confidence: 52%
“…Several studies confirm these data, showing similar outcomes regardless of donor type. [18][19][20] We found a survival benefit with lower dose ATG-F. Previous studies, of which some are published as abstracts only, found some advantage for ATG treatment.…”
Section: Discussionsupporting
confidence: 52%
“…53 A French study initially saw no significant impact of donor age among MDS and AML patients undergoing transplantation. 54 In contrast, a later analysis by the French group found that donor age ≥60 years had a significant adverse impact on overall recipient survival. 55 A CIBMTR analysis from 2013 reported that outcomes were superior in recipients of grafts from HLAidentical sibling donors >50 years old compared to those with grafts from HLA-matched unrelated donors <50 years of age.…”
Section: Older Donorsmentioning
confidence: 99%
“…[1][2][3] With increasing use of unrelated donors (URDs) for allogeneic HCT, large studies have evaluated outcomes for patients with sibling donor vs URD, with most demonstrating similar longterm survival among the 2 donor groups. [4][5][6][7][8][9][10][11][12][13][14] However, when given the option of a sibling donor or URD, sibling donors are typically preferred for convenience and possibly to reduce GVHD and to improve survival. Both donor-recipient sex mismatching and the effect of donor parity have been evaluated as possible influences on transplant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%